DNA-typing improves illegal wildlife trade surveys: Tracing the Cameroonian bushmeat trade. (May 2022) - Din Dipita, Alain; Missoup, Alain Didier; Tindo, Maurice; Gaubert, Philippe
Abstract: Although the bushmeat trade is a significant component of the Anthropocene crisis in the tropics, the reliability of species-level identification is generally lacking from bushmeat surveys. We conducted a comprehensive study of 23 bushmeat markets in Cameroon and one seizure from a French airport using a multi-gene DNA-typing approach and a dedicated species-assignment pipeline (DNABUSHMEAT). We identified 39 species-level taxa from 318 collected bushmeat items, including nine Cetartiodactyla, six Carnivora, three Pholidota, seven Rodentia, 12 Primates, one Squamata and one Crocodilia. DNA-typing allowed detecting three species previously unreported from the Cameroonian trade and clarifying the status of taxa subject to cryptic diversity (rodents) and shallow diagnostic characters (small carnivores, antelopes and guenons). Only 7% of the samples could not be assigned to the species-level, including two guenons and one snake, because of fluctuant taxonomy and weak representation in nucleotide databases. Almost half (43%) of the morphological identifications were corrected or refined by our DNA-typing approach. Generalized linear models showed that smoked specimens and primates were significantly suffering from inaccurate species identification. We also observed that customs (Paris) and market-recruited assistants (Cameroon) peaked at very high rates of inaccurate species identifications (87 and 100%, respectively), calling for cautiousness when third parties are involved in bushmeat surveys. Overall, >50% of the bushmeat species traded in Cameroon were nationally protected. Because accurate species identification is a central component of conservation strategies, we posit that our DNA-typing approach is a valuable asset for improving the traceability of the domestic and international bushmeat trade.